Administrative Leadership in Times of a Global Health Crisis: Voices and Images From the Field - DeMartino, Linsay; Weiser, S. Gavin (Frontiers in Education, 2021)
The novel coronavirus (COVID-19) pandemic took the world into crisis. We saw the virus alter a multitude of spheres worldwide, including our healthcare, economies, politics, social processes, and education. In fact, the impact of COVID-19 on educational administration took our leaders into forced emergency measures. Our study aims to better understand the experiences of educational administrators under crisis to ascertain what might be learned on how educational institutions may better respond to crisis in the future. These stories were collected from educational leaders, both from K-12 and higher education, throughout the United States. In brief, this article is framed in the theory and literature associated with the complexity of leading in times of crisis. We explore the resiliency of leadership forged in crisis (Hutson and Johnson 2016; Koehn 2019) and the rethinking of administrative (Sergiovanni 1994; Stefkovich and Begley) as administration as a caring (Noddings 2002; Smylie, Murphy, and Louis 2016) and trustful acts (Kutsyuruba and Walker 2015; Wahlstrom and Louis 2008). Our research began as a standard phenomenological interview study, but transitions into a two-round project, where after the first interview, participants were invited to share some images that typify and speak to the experiences being educational administrators during this time. We are engaging in sensitive topics that are on-going and changing. Moreover, throughout, we are asking for images that speak to their experiences. Across both K-12 and higher education, our results indicated varied responses, from immediate to delayed administrative action. However, albeit they looked contextually different, there are clear indications the participants valued continuous, transparent communication, authentic caring, trust, and agency. In our discussion, we elaborate on the distinction between what the institutional response was as compared to what was valued by our educational leaders. Finally, as a contribution to the field, we seek to provide guidance for future administrators in crisis based on our own experiences and the recommendations provided by our educational leaders. Keywords: COVID-19, educational administration, crisis leadership, caring leadership, trust in leadership, phenomenological interview study, photovoice